(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
This article describes the effects of lack of grammar knowledge on integrated skills. The article defines the issues related to grammar on integrated skills. It also shows the importance of grammar in learning foreign languages. There are some recommended solutions to solve the problems for foreign language learners. They are absolutely helpful to follow so as to advance integrated skills by increasing awareness of grammar knowledge